Ultrastructural Studies of Treponemes: Location of Axial Filaments and Some Dimensions of Treponema pallidum (Nichols strain), Treponema denticola, and Treponema reiteri - Sykes, John A. (1973)
Ultrathin sections of Treponema pallidum (Nichols strain), T. denticola (microdentium), and T. reiteri have been studied in the electron microscope to determine the location of the axial filaments and some of the dimensions of these organisms. The axial filaments of T. pallidum (Nichols strain) have been seen to be tubular in cross section with an overall diameter of 21.0 ± 0.73 nm, and an electron-lucent core of 8.0 nm. The filaments were found to lie on the outside of the organism which had only one membranous structure surrounding the protoplasmic core. These findings were in contrast to those obtained for T. denticola and T. reiteri where the axial filaments did not exhibit a hollow core and were located between an outer membrane and an inner membrane surrounding the protoplasmic core. The outside diameter of T. denticola was determined to be 224.9 ± 2.83 nm, and that of T. reiteri as 331.0 ± 4.15 nm, contrasting with T. pallidum (Nichols strain) which had a diameter of 163.0 ± 1.9 nm.